1980
DOI: 10.2220/biomedres.1.76
|View full text |Cite
|
Sign up to set email alerts
|

<b>MOTILIN-LIKE IMMUNOREACTIVITY IN PORCINE, CANINE, HUMAN AND RAT </b><b>TISSUES </b>

Abstract: Eight antisera were obtained from three rabbits and two guinea pigs immunized with synthetic porcine motilin and from three guinea pigs immunized with [15-Glutamine]-rnotilin. Specificities of the antisera were characterized and three of them having different specificities were used in radioimrnunoassay to examine motilin immunoreactivity in extracts of canine, porcine, human and rat gastrointestinal tissues. Immunoreactive motilin in rat tissue extract showed a very low cross-reaction in all of the assay syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…3A). This might be in accordance with the observations by Yanaihara and his coworkers [9,10], who reported that the assay values for motilin depend on antisera with different specificity to epitopes in the motilin molecule.…”
Section: Discussionsupporting
confidence: 93%
“…3A). This might be in accordance with the observations by Yanaihara and his coworkers [9,10], who reported that the assay values for motilin depend on antisera with different specificity to epitopes in the motilin molecule.…”
Section: Discussionsupporting
confidence: 93%
“…These tests for specificity included pre-absorption of every primary antiserum to a gut peptide with the relevant antigen (see Table 2) for 16-22 h at 4 ~ C, substitution of the primary antiserum with non-immune serum of the species in which the primary antiserum had been raised or, in the case of the monoclonal antibody, with a Yanaihara et al (1980) b These gifts are gratefully acknowledged a These gifts are gratefully acknowledged mouse ascites fluid containing IgG2a, and with diluent alone. All antisera to gut peptides were pre-absorbed in turn with serotonin and each of the gut peptides available (see Rawdon and Andrew ]981) and applied to sections of normal chick gut to test for crossreactivity.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously characterized five anti-synthetic porcine motilin sera and each of the antisera was found to have different region-specificities (Yanaihara et al, 1978a(Yanaihara et al, , 1980. Radioimmunoassays using these antisera gave different dose-response curves for motilin immunoreactivity in the canine and rat duodenal extracts (Yanaihara et al, 1980).…”
mentioning
confidence: 99%